The Effect of Organizational Commitment and Motivation on Empoyee Performance : Evidence From SMEs - Alwi Muhammad Adam (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2024)
SMEs are currently developing very rapidly, and have contributed to the Indonesian economy. This study aims to see the effect of organizational commitment and work motivation on employee performance at SMEs in Rantauprapat City. The research method uses quantitative methods. The number of samples collected was 153. So that the sample in the study amounted to 153 samples. The results of the study indicate that there is a positive and significant influence between organizational commitment and work motivation on employee performance at SMEs in Rantauprapat City.